Microbial communities involved in anaerobic degradation of unsaturated-and saturated-LCFA in methanogenic bioreactors - Sousa, D. Z. (2006)
Long chain fatty acids (LCFA) are frequently found in wastewaters as the main product of lipid hydrolysis. These compounds hold a high energetic potential and thus are attractive substrates for methane production. Insight into the microbial populations involved in anaerobic LCFA-degradation is important for the development and improvement of technologies for lipids/LCFA-rich wastewater valorisation. This study identifies putative LCFA-degrading bacteria by combining selective enrichments with molecular techniques. Two distinct enrichment series of anaerobic cultures growing on unsaturatedand saturated-LCFA were obtained by successive transfers in medium containing oleate (C18:1) and palmitate (C16:0), respectively, as the sole carbon and energy source. This procedure resulted in two stable and highly enriched cultures that could convert oleate and palmitate to acetate and methane. Changes in the microbial composition during the enrichment were analyzed by 16S rRNA gene PCRDGGE profiling. Upon enrichment a decrease in microbial diversity was observed. Prominent bands in the DGGE profiles of stable enriched cultures were identified by 16S rRNA gene sequencing, and nearly full sequences were compared using ARB software. A major part of the retrieved 16S rRNA gene sequences was most similar to those of uncultured bacteria. Organisms corresponding to dominant DGGE bands in oleate- and palmitate-enrichment cultures clustered with fatty-acid oxidizing syntrophic bacteria within Syntrophomonadaceae and Syntrophaceae families. Despite the absence of sulphate in the medium, a Desulfovibrio-like organism was detected as a dominant band in the DGGE profile of the oleate-enrichment culture. In other studies Desulfovibrio species have been detected in methanogenic reactors without added sulphate. They were proposed to grow acetogenically. The role of such bacteria in the oleate-enrichment culture is not clear yet, and this needs further investigation. A low methane yield (12%) was observed in the oleate-enrichment and acetate, produced according to the expected stoichiometry, was no further converted to methane. In the palmitate-enrichment culture, the acetate produced was completely mineralised and a total methane yield of about 83% was achieved from palmitate degradation. Furthermore, the oleate-enrichment culture was able to use palmitate without detectable changes in the DGGE profile. However, the palmitate-specialised consortia degraded oleate only after a lag phase of three months, after which the DGGE profile was changed. A dominant band appeared and sequence analysis showed affiliation with the Syntrophomonas genus. This band was also present in the oleate-enrichment culture, suggesting that this bacterium is important for oleate degradation, emphasizing possible differences between the degradation of unsaturated- and saturated-LCFA.